A comparison study on the performance between Tetrametylammonium chloride and PolyvinylPyrrolidone as drilling mud additives for gas hydrates - Yuha, Y.B.M. (Elsevier Ltd, 2020)
The utilization of ionic liquids as additives in mud system to improve the rheological properties for drilling hydrate sediments has received much attention recently. However, their performance needs to be compared with commercial inhibitors to effectively enhance their replacement process. Therefore, in this work, the effect of one of the best reports ionic liquid, Tetrametylammonium chloride (TMACl) was used for hydrate management in the drilling process and was compared with PolyvinylPyrrolidone (PVP -a commercial hydrate additive). The experiments were achieved by formulating drilling fluid with the compositions of freshwater, 3.0 wt NaCl, 3.0 wt KCl and 0.8 wt Xanthan Gum and 1 wt of TMACl/PVP, and verifying the rheological, physiochemical, and hydrate inhibition properties of the mud system prepared. A kinetic hydrate reactor is used to examine the hydrate inhibition properties at 8 MPa and -2 Â°C and a TA instrument rheometer DHR1 was used to study the rheological properties of the mud systems prepared. The results showed that TMACl stabilized drilling mud thermal degradation by 400, which PVP doubles the thermal degradation rate of drilling mud. In addition, TMACl could provide suitable shear thinning behavior than PVP. Though the effect of both PVP and TMACl on the CH4hydrate formed is within the same range, PVP delayed the time taken for hydrate formation by 25 from TMACl. Therefore, the findings in this study provided guidelines and information to the successful application and replacement of conventional hydrate inhibitions with ionic liquids. Â© 2020 Elsevier Ltd. All rights reserved.